2012
DOI: 10.1371/journal.pone.0037998
|View full text |Cite
|
Sign up to set email alerts
|

Relation of IL28B Gene Polymorphism with Biochemical and Histological Features in Hepatitis C Virus-Induced Liver Disease

Abstract: Background/AimsPolymorphism at the IL28B gene may modify the course of hepatitis C virus (HCV) chronic infection. Our aim was to study the influence of IL28B rs12979860 gene polymorphism on the biochemistry and pathology of HCV-induced disease in the clinical course from mild chronic hepatitis C to hepatocellular carcinoma.MethodsWe have determined the rs12979860 single nucleotide polymorphism (SNP) upstream IL28B gene in two groups of patients with HCV-induced chronic liver disease: 1) 268 patients (159 men) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
1
29
1
Order By: Relevance
“…This finding corresponds with the result of a Genome Wide Association study that demonstrated that the rs12979860CC was significantly associated with ALT levels which is regarded as a necro inflammatory marker of the liver cells. Another study showed that the carriers of the rs12979860CC genotype had higher values for ALT comparing with carriers of the rs12979860CT/TT genotypes among Spanish individuals, which is a similar result to our study [17]. As several previous studies have reported, IL-28B CC genotype is connected to a strong immune response against hepatitis viruses, which on a positive side leads to higher viral clearance, yet negatively, to a more advanced cell injury which explains the result of higher levels of ALT and AST in CC genotype group, and supporting an idea that the IL-28B genotypes are directly linked to the pathogenesis of liver damage in delta hepatitis [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding corresponds with the result of a Genome Wide Association study that demonstrated that the rs12979860CC was significantly associated with ALT levels which is regarded as a necro inflammatory marker of the liver cells. Another study showed that the carriers of the rs12979860CC genotype had higher values for ALT comparing with carriers of the rs12979860CT/TT genotypes among Spanish individuals, which is a similar result to our study [17]. As several previous studies have reported, IL-28B CC genotype is connected to a strong immune response against hepatitis viruses, which on a positive side leads to higher viral clearance, yet negatively, to a more advanced cell injury which explains the result of higher levels of ALT and AST in CC genotype group, and supporting an idea that the IL-28B genotypes are directly linked to the pathogenesis of liver damage in delta hepatitis [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Another drawback was the absence of histopathological examination, which is regarded as the gold standard for evaluating necro inflammation, liver fibrosis and cirrhosis. However, a recent study has not detected a parallel between IL-28B polymorphism and the necro inflammatory grade and the stage of fibrosis through liver biopsy in CHC patients [17]. Moreover, liver biopsy for chronic Hepatitis B infection before antiviral therapy in chronic hepatitis B (CHB) patients is not routinely part of contemporary practice, especially for those with obviously active CHB (ALT above 2 times ULN and HBV DNA>2000 IU/mL) [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…After our selection, 7 casecontrol studies including 1152 HCC and/or LC cases and 1326 controls fulfilled the inclusion criteria (Barreiro et al, 2011;Fabris et al, 2011;Falleti et al, 2011;Agundez et al, 2012;El-Awady et al, 2012;Eurich et al, 2012;Ren et al, 2012). The quality of the studies was considered acceptable for our meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 5 case-control studies Agundez et al, 2012;El-Awady et al, 2012;Eurich et al, 2012;Ren et al, 2012), which had been performed to study the rs12979860 poly morphism and HCC risk. The results of the meta-analysis are shown in Table 3.…”
Section: Evaluation Of the Il-28b Rs12979860 Polymorphism And Associamentioning
confidence: 99%
“…Associations between IL-28B variants and HCC development [22] and recurrence [23] have recently been reported. Moreover, an association between the IL-28B rs12979860 CC genotype and higher ALT levels has also been described [24] . It is possible that the IL-28B genotype is associated with inflammatory activity in the liver and the progression of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 98%